From Sticky to Slippery: Self-Functionalizing Lubricants for in Situ Fabrication of Liquid-Infused Surfaces - Chiera, Salvatore; Koch, Vanessa; Bleyer, Gudrun; Walter, Teresa; Bittner, Carina; Bachmann, Julien; Vogel, Nicolas (ACS Applied Materials and Interfaces, 2022)
Liquid-infused surfaces offer a versatile approach to create self-cleaning coatings. In such coatings, a thin film of a fluid lubricant homogeneously coats the substrate and thus prevents direct contact with a second, contaminating liquid. For stable repellency, the interfacial energies need to be controlled to ensure that the lubricant is not replaced by the contaminating liquid. Here, we introduce the concept of self-functionalizing lubricants. Functional molecular species that chemically match the lubricant but possess selective anchor groups are dissolved in the lubricant and self-adhere to the surface, forming the required surface chemistry in situ from within the applied lubricant layer. To add flexibility to the self-functionalizing concept, the substrate is first primed with a thin polydopamine base layer, which can be deposited to nearly any substrate material from aqueous solutions and retains reactivity toward electron-donating groups such as amines. The temporal progression of the in situ functionalization is investigated by ellipsometry and quartz crystal microbalance and correlated to macroscopic changes in contact angle and contact angle hysteresis. The flexibility of the approach is underlined by creating repellent coatings with various substrate/lubricant combinations. The prepared liquid-infused surfaces significantly reduce cement adhesion and provide easy-to-clean systems under real-world conditions on shoe soles.
CRIS-Team Scopus Importer:2022-04-22
Keywords: coatings; liquid-infused surfaces; polydopamine; self-cleaning; surface functionalization

Optimizing Color Saturation in Colloidal Photonic Crystals by Control of Absorber Amount and Distribution - Bittner, Carina; Bleyer, Gudrun; Nees, Nico; Carneiro, Miguel; Pflug, Lukas; Stingl, Michael; Vogel, Nicolas (Advanced Materials Interfaces, 2024)
Nanostructured materials that mimic structural coloration in nature can be synthetically created by colloidal self-assembly. To maximize optical effects, the natural world integrates melanin as a broadband absorber to remove incoherently scattered light. Polydopamine (PDA) is used as a synthetic analog of natural melanin to systematically investigate the influence of absorber quantity and distribution on color saturation in colloidal photonic crystals. The absorbing PDA is integrated into two distinct ways: homogenous colloidal crystals are produced from core–shell particles with incrementally increasing polydopamine shells, and heterogeneous colloidal crystals are formed by co-assembly of varying ratios of polystyrene (PS) and absorbing PS@PDA particles. The chromaticity is quantified by converting the measured spectra to reconstructed colors in the L*a*b* color sphere to identify structures with optimal color saturation. Simulations based on the discrete dipole approximation (DDA) indicate that a homogeneous absorber distribution is most efficient in creating saturated structural coloration. Experiments, however, demonstrate that the heterogeneous absorber incorporation outperforms the homogeneous strategies, as it allows for a more precise adjustment of the absorber content in the required concentration range. These results underline the importance of incorporating absorbers and indicate efficient ways in which colloidal photonic crystals with saturated structural colors can be prepared.
CRIS-Team Scopus Importer:2024-02-16
Keywords: colloidal crystals; polydopamine; self-assembly; structural colors

Substrate-Independent Design of Liquid-Infused Slippery Surfaces via Mussel-Inspired Chemistry - Chiera, Salvatore; Bittner, Carina; Vogel, Nicolas (Advanced Materials Interfaces, 2021)
Self-cleaning and repellent coatings ensure enduring performance of surfaces in many areas of technology and everyday life. An ideal repellent coating is efficient in removing contaminations, yet easy to apply on a wide range of surface materials. To devise such a coating, two bioinspirations are combined that show opposing interfacial properties: the peristome of a pitcher plant and the versatile mussel-inspired chemistry of polydopamine (PDA). The possibility of PDA to bind to different surface materials is taken to provide a material-independent coating strategy. Its reactivity toward amines to cofunctionalize the coating with monoaminopropyl-polydimethylsiloxane is utilized to control the surface chemistry. This process, in effect, adheres silicone polymer chains to any desired surface material. Finally, inert silicone oil is added to the reaction mixture to provide in situ lubrication of the coating. Together, the process creates lubricant-infused surfaces in a one-step process independent of the underlying substrate. It is shown that the reaction mixture can be deposited by dip or spray coating, providing procedures to coat large surfaces and complex samples such as textiles and wood. The combination of the mussel-inspired chemistry with the pitcher plant-inspired control of wettability provides an experimentally simple coating process to impart efficient repellency and self-cleaning characteristics to virtually any surface material.
CRIS-Team Scopus Importer:2021-05-14
Keywords: liquid infused surfaces; liquid repellency; mussel-inspired chemistry; polydopamine; slippery surfaces; spray coating